Comparison between self-sampling and gynecologist sampling of cervical specimen for pap cytology and HPV DNA detection among women in Jempol, Negeri Sembilan, Malaysia - Ibrahim, Zaidah (2015)
Self-sampling for cervical screening have shown good acceptance among hard to reach women and in low healthcare resource setting area. This study was to measure the agreement and available differences between Kato self-sampling device (KSSD) and gynecologist sampling for PAP cytology and Human Papillomavirus DNA (HPV DNA) detection. Cytology specimens (486 specimen pairs) and HPVDNA specimens (226 specimen pairs) from women attended screening at 2 Primary Health Clinics, in Jempol Negeri Sembilan, Malaysia were assessed. All women underwent self-sampling first followed by gynecologist sampling. The prepared PAP cytology slides were evaluated for specimen adequacy, presence of endocervical cells or transformation zone cells and cytological interpretation for cells abnormalities. For HPV testing, samples were measured for DNA concentration and quality and underwent HPV DNA detection using nested PCR (primer MY 9/11 and GP5+/6+). Specific HPV genotype was determined by gene sequencing which referred to the online NCBI gene bank. The result between self-sampling and gynecologist sampling were compared using statistical Wilcoxon signed rank test, Kappa agreement and McNemar Chi Square test. In PAP specimen adequacy, KSSD showed 100% agreement with gynecologist sampling with all samples showed satisfactory for evaluation however had only 32.3% agreement for presence of endocervical cells. For cytological interpretation both sampling showed 100% agreement with only 1 case detected HSIL favor CIN2. Median DNA concentration for KSSD and gynecologist sampling were 30.0 ng/ul and 36.0 ng/ul respectively (p=0.045). For detection of HPV DNA, 86.2% agreement( k = 0.64 , 95% CI 0.524-0.756 ,p= 0.001) was found between technique of sampling with KSSD and gynecologist sampling HPV positive were 22.6% and 27% respectively (p>0.05). Both techniques detected HPV 11, 16, 18, 31, 33 and 45. KSSD and gynecologist identified high risk HPV 17.3% and 23.9 % respectively (p= 0.014). HPV 18 showed a significant different (p=0.02) but HPV type 16 showed no significant different (p=1.00) between the sampling techniques. As conclusion,the self-sampling using Kato device is comparable to the gynecologist sampling for PAP cytology and HPV DNA detection and a good potential as an alternative to increase cervical screening participation among women especially in rural area or low healthcare setting.